2006
DOI: 10.1121/1.2372454
|View full text |Cite
|
Sign up to set email alerts
|

Laser interferometry measurements of middle ear fluid and pressure effects on sound transmission

Abstract: An otitis media with effusion model in human temporal bones with two laser vibrometers was created in this study. By measuring the displacement of the stapes from the medial side of the footplate, the transfer function of the middle ear, which is defined as the displacement transmission ratio (DTR) of the tympanic membrane to footplate, was derived under different middle ear pressure and fluid in the cavity with a correction factor for cochlear load. The results suggest that the DTR increases with increasing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
68
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(91 citation statements)
references
References 20 publications
21
68
2
Order By: Relevance
“…The effect of middle ear pressure on TM mobility has been investigated in human temporal bones and animals (Teoh et al, 1997;Lee and Rosowski, 2001;Rosowski and Lee, 2002;Murakami et al, 1997;Dirckx and Decraemer, 1992;Huttenbrink 1998;Gan et al, 2006;Dai et al, 2007). The results of Murakami et al and Gan et al show that the middle ear pressure mainly decreased the TM movement at low frequencies (f <1k Hz).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…The effect of middle ear pressure on TM mobility has been investigated in human temporal bones and animals (Teoh et al, 1997;Lee and Rosowski, 2001;Rosowski and Lee, 2002;Murakami et al, 1997;Dirckx and Decraemer, 1992;Huttenbrink 1998;Gan et al, 2006;Dai et al, 2007). The results of Murakami et al and Gan et al show that the middle ear pressure mainly decreased the TM movement at low frequencies (f <1k Hz).…”
Section: Introductionmentioning
confidence: 88%
“…No substantial amount of water was found in the mastoid processes of the four bones. Figure 1 shows the temporal bone experimental setup with a laser vibrometer and a tympanometer, which was similar to studies reported by Gan et al (2006) and Dai et al (2007). Briefly, the temporal bone was placed in a temporal bone holder and the bone assembly was set on a vibration isolation table.…”
Section: Human Temporal Bone Preparationmentioning
confidence: 96%
See 2 more Smart Citations
“…90 dB SPL pure tones were applied in the ear canal at 2 mm away from the umbo and the acoustic-structure coupled FE analysis was performed between the ear canal, TM, and middle ear cavity over the frequency range of 0.2-10 kHz. Figure 2A shows the middle ear transfer function derived from the FE model of human ear (baseline model-Case 1) as the displacement-frequency curves of the TM at the umbo and the stapes footplate in comparison with the experimental measurements reported from 17 temporal bones by Gan et al [4,5]. The modelling results from the FE model without synovial ISJ are also shown in the figure.…”
Section: Mechanical Properties Of Isj Components and Fe Analysismentioning
confidence: 72%